Heated-balloon ablation as a novel less invasive local treatment for bile duct strictures: A first experimental study - Tadahisa Inoue; Takuya Masuda; Tomoharu Koiso; Mayu Ibusuki; Yusuke Oshima; Yuta Kato; Rena Kitano; Hiromu Kutsumi (PLoS ONE, 2025)
Background Endobiliary radiofrequency ablation (RF-A) is a promising therapeutic option for bile duct strictures. However, conventional catheter RF-A has several limitations, and its usefulness and application remain debated. This study aimed to examine the feasibility of a novel heated-balloon ablation (HB-A). Methods A prototype HB-A catheter, along with an assembly created from freshly resected porcine liver and a specific jig, was used in this study. The test HB-A setting was set in six patterns: 70°C in the target temperature with 2.5 min in the target temperature maintenance time, 70°C with 5 min, 75°C with 2.5 min, 75°C with 5 min, 80°C with 2.5 min, and 80°C with 5 min. The study outcomes included the ablation range and temperature propagation associated with HB-A. Results The lengths and depths of the ablation area were 15.8 ± 1.3 and 1.5 ± 0.1, 18.0 ± 0.7 and 2.1 ± 0.1, 18.8 ± 0.4 and 2.3 ± 0.2, 18.5 ± 0.9 and 2.5 ± 0.1, 19.8 ± 0.8 and 2.5 ± 0.1, and 20.5 ± 0.5 and 3.4 ± 0.1 mm in 70°C for 2.5 min, 70°C for 5 min, 75°C for 2.5 min, 75°C for 5 min, 80°C for 2.5 min, and 80°C for 5 min, respectively. Excessive ablation was not observed during any procedure. The temperature cutoff for achieving or not achieving the ablation effect was between 55 and 60°C for every setting. Conclusions The novel HB-A treatment has good temperature and ablation range control with high reproducibility under the same settings while preventing excessive ablation. This study paves the way for further evaluation of this procedure and its early clinical application.